Pathophysiological Mechanisms Underlying Idiopathic Normal Pressure Hydrocephalus: A Review of Recent Insights - Bonney, Phillip A.; Briggs, Robert G.; Wu, Kevin; Choi, Wooseong; Khahera, Anadjeet; Ojogho, Brandon; Shao, Xingfeng; Zhao, Zhen; Borzage, Matthew; Wang, Danny J. J.; Liu, Charles; Lee, Darrin J. (Frontiers in Aging Neuroscience, 2022)
The pathophysiologic mechanisms underpinning idiopathic normal pressure hydrocephalus (iNPH), a clinically diagnosed dementia causing disorder, continue to be explored. An increasing body of evidence implicates multiple systems in the pathogenesis of this condition, though a unifying causative etiology remains elusive. Increased knowledge of the aberrations involved has shed light on the iNPH phenotype and has helped to guide prognostication for treatment with cerebrospinal fluid diversion. In this review, we highlight the central role of the cerebrovasculature in pathogenesis, from hydrocephalus formation to cerebral blood flow derangements, blood-brain barrier breakdown, and glymphatic pathway dysfunction. We offer potential avenues for increasing our understanding of how this disease occurs.